Brainstem activation of GABAB receptors in the nucleus tractus solitarius increases gastric motility - Bellusci, Lorenza; Kim, Elizabeth; Garcia DuBar, Selena; Gillis, Richard A.; Vicini, Stefano; Sahibzada, Niaz (Frontiers in Neuroscience, 2022)
Background and aim Local GABAergic signaling in the dorsal vagal complex (DVC) is essential to control gastric function. While the inhibitory GABAA receptor action on motility in the DVC is well-documented, the role of the GABAB receptor on gastric function is less well-established. Microinjection of baclofen, a selective GABAB receptor agonist, in the dorsal motor nucleus of the vagus (DMV) increases gastric tone and motility, while the effect on motility in the nucleus tractus solitarius (NTS) needs to be investigated. Previous in vitro studies showed that GABAB receptors exert a local inhibitory effect in unidentified NTS neurons. Since the NTS and DMV nuclei have differential control of gastric motility, we compared GABAB receptor activation in the NTS to that reported in the DMV. We microinjected baclofen unilaterally in the NTS while monitoring intragastric pressure and compared its action to optogenetic activation of somatostatin (SST) neurons in transgenic sst-Cre::channelrhodopsin-2 (ChR2) mice. We also performed patch-clamp recordings from SST and DMV neurons in brainstem slices from these mice. Methods In vivo drug injections and optogenetic stimulation were performed in fasted urethane/α-chloralose anesthetized male mice. Gastric tone and motility were monitored by an intragastric balloon inserted in the antrum and inflated with warm water to provide a baseline intragastric pressure (IGP). Coronal brainstem slices were obtained from the sst-Cre::ChR2 mice for interrogation with optogenetics and pharmacology using electrophysiology. Results The unilateral microinjection of baclofen into the NTS caused a robust increase in gastric tone and motility that was not affected by ipsilateral vagotomy. Optogenetic activation of SST neurons that followed baclofen effectively suppresses the gastric motility in vivo. In brain slices, baclofen suppressed spontaneous and light-activated inhibitory postsynaptic currents in SST and gastrointestinal-projection DMV neurons and produced outward currents. Conclusion Our results show that GABAB receptors in the NTS strongly increase gastric tone and motility. Optogenetic stimulation in vivo and in vitro suggests that these receptors activated by baclofen suppress the glutamatergic sensory vagal afferents in the NTS and also inhibit the interneurons and the inhibitory neurons that project to the DMV, which, in turn, increase motility via a cholinergic excitatory pathway to the stomach.